2010
DOI: 10.4038/sljpsyc.v1i2.2577
|View full text |Cite
|
Sign up to set email alerts
|

A study of intimate partner violence among females attending a Teaching Hospital out-patient department

Abstract: Background Intimate partner violence (IPV) is considered a public health problem with physical and psychological consequences. Aims To describe the prevalence of IPV among married females attending the outpatient department of North Colombo Teaching Hospital and their attitude towards abuse. Methods A pre-tested self-administered questionnaire on physical, verbal, sexual and emotional abuse was given to the first 50 consenting married females attending the outpatient department on each day for five consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly, Abramsky et al (2011) revealed that there was a strong relationship between problematic alcohol use by both husbands and wives and IPV. In many studies, alcohol consumption by husbands was identified as a major factor that causes a positive impact on partner violence behavior against women (Kuruppuarachchi et al, 2010;Agumasie et al,2013;Laeheem, 2016).…”
Section: Ln(mentioning
confidence: 99%
“…Similarly, Abramsky et al (2011) revealed that there was a strong relationship between problematic alcohol use by both husbands and wives and IPV. In many studies, alcohol consumption by husbands was identified as a major factor that causes a positive impact on partner violence behavior against women (Kuruppuarachchi et al, 2010;Agumasie et al,2013;Laeheem, 2016).…”
Section: Ln(mentioning
confidence: 99%
“…Stigmatizing attitudes among nurses towards women survivors who seek hospital care have also been reported from Sri Lanka (Jayasuriya et al, 2011). Patriarchal attitudes and gender biases internalized by women themselves are evident in the Sri Lankan society, with many women believing that they should tolerate IPV (Kuruppuarachchi et al, 2010). Further, a survey of 1658 men and 653 women between the ages of 19-49, in four districts in Sri Lanka, revealed more gender inequitable attitudes among females than males; for example, more female than male participants believed that one should consider whether a rape victim had a "bad reputation" (De Mel et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Some survivours use gender norms as the basis to justify being beaten by the husband. Study done at Teaching Hospital Colombo North, by Kuruppuarachchi (2010), revealed that "Majority of the females believed that the violence by the male partner should be tolerated. [6] "Male is expected to be more aggressive and more sexually active".…”
mentioning
confidence: 99%